Implementasi Teba Modern Sebagai Solusi Berkelanjutan Pengelolaan Sampah Organik Di Kelurahan Betungan - Pratama, Arie Nugraha; Syaputri , Alinza; Pratama, Dimas Yoga Arif; Amalia, Redha; Oktarisna, Resty; Kresnawati, Kresnawati; Susena, Karona Cahya; Handayani, Tita (Jurnal Karya Nyata Pengabdian, 2025)
Improper waste management, especially organic waste, can cause pollution and health problems. In Betungan Village, precisely in RT 26 RW 03, there are already cleaning staff who collect waste from every house every afternoon, but sometimes the cleaning staff are reluctant to collect organic waste such as branches, twigs, or animal carcasses that cause the environment to become dirty and smelly. One solution that can be applied is the creation of a modern Teba, Modern Teba functions as a composter that can be used by every member of the household. Modern Teba is a channel designed with a diameter of 80 centimeters which is equivalent to two circular concretes. The two concretes are placed in the ground with the bottom left open, the bottom or soil will function as a support for the rotting organic ecosystem. Making a hole deeper than about 3 meters is not recommended, because it will cause less than optimal waste decomposition, then the top of the hole will be closed and a small hole will be made to release dangerous gases and pests. This innovation helps facilitate waste sorting from the start, reduces the volume of waste disposed of, and produces compost that is beneficial to the environment. This approach is expected to increase public awareness of sustainable waste management.